PANDUAN LAPANGAN JENIS-JENIS BURUNG DI LINGKUNGAN UNIVERSITAS LAMPUNG BERBASIS ANDROID - Rifki Wardana; Aristoteles Aristoteles; Jani Master (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Bird is one of animals that can be found di various habitats, its existence spread from the forest, the plantation until the urban. Bird is also one group of animals that close to human life. The aim of this system is to be an alternative media to facilitate people who want to get information about the types of birds in Lampung University. In this research, android- based field guide to the types of birds of Lampung university areais using java programming language. The method which is used in this application is Waterfall, and Unified Modeling Language (UML) design. This application contains 61 types of birds that can be found in Lampung University. The data of this application are pictures of birds, name of birds, Latin name, English name, family name, description and status that can help the user to recognize the types of birds which they find in Lampung University. The data result used Equivalence Partitioningtesting, showed that the rules of the system can work suitable with the function and the system can give information well. This application is a category of variable user friendly with average 4,30 (very well) and a category of interactive variable with average 4,28 (very well).Â Keywords: Android, Bird, Field guide, pemrograman Java, Unified Modeling Language (UML)